Perbandingan Kualitas Soal Buatan Guru Akuntansi Antara Sekolah Terakreditasi A dan B - Apsari Yunita; Edy Purnomo; Tedi Rusman (JEE (Jurnal Edukasi Ekobis), 2017)
This research was conducted to find out the comparison of the quality of the itemcreated by teachers of Accounting Class between the Accreditation A andAccreditation B Private Vocational School quantitatively. This research methodwas expost facto. The population of this research was the item of final-term test inPrivate SMK in Tangerang City with sample used are 240 items from 6 schoolswith cluster area sampling technique. Technique of collecting data of this research is through documentation. Hypothesis testing used two independent sample t-tests. Based on the analysis of the data, it obtained the results (1) The quality of question reviewed from the level of difficulty, differentiation, validity, and reliability problems made by teachers of Accounting subject in School Accreditation A is not better than school with Accreditation B (2) The quality of questions reviewed from the effectiveness of the distractor created by the teachers of Accounting subject at schools with Accreditation A is better than school with accreditation B.Penelitian ini dilakukan untuk mengetahui perbandingan kualitas soal buatan guru Akuntansi antara SMK Terakreditasi A dan Terakreditasi B secara kuantitatif. Metode penelitian ini yaitu expost facto. Populasi penelitian ini yaitu soal ujian akhir semester pada SMK Swasta di Tangerang dengan sampel yang digunakan sebanyak 240 soal dari 6 sekolah dengan teknik pengambilan sampel cluster area sampling. Teknik pengumpulan data adalah dokumentasi. Pengujian hipotesis menggunakan t-tes dua sampel independen. Berdasarkan analisis dan pengujian diperoleh hasil (1) Kualitas soal yang ditinjau dari tingkat kesukaran, daya beda, validitas, reliabilitas soal buatan guru Akuntansi SMK Terakreditasi A tidak lebih baik dari Terakreditasi B (2) Kualitas soal yang ditinjau dari efekivitas pengecoh soal buatan guru Akuntansi SMK Terakreditasi A lebih baik dari Terakreditasi B.Kata kunci: akreditasi, akuntansi, soal, guru.